Transpacific Environmental Imagination: Comparative Analysis of Indigeneity in The Healers and Burung Kayu. - Indriyanto, Kristiawan; Syahfitri, Dian (SARE: Southeast Asian Review of English, 2024)
This study delves into the representation of indigenous values in two literary works, the Healers and Burung Kayu, set in Hawaii and Mentawai, Indonesia, respectively. Drawing upon the framework of Critical Island Studies, it examines the complexities of island landscapes, societies, and histories through literature. The analysis focuses on the portrayal of kahuna and sikerei, custodians of indigenous knowledge in their respective communities, highlighting their roles and the historicity of repression and persecution. Both narratives affirm the interconnectedness of all entities based upon familial ties and creation myth of cosmology. The historicity of each narrative posits the unique circumstances, with Hawaii experiencing a resurgence of traditional beliefs post-Renaissance while Mentawai faced intensified persecution during the Indonesian New Order era. This study underscores the significance of indigeneity as a shared outlook among various ethnic communities worldwide, shaping their cultural identities and resilience. Based upon the analysis, comparative studies of indigeneity offer a promising avenue for further exploration, delineates the dynamics of island communities and their struggles to reclaim their heritage in contemporary society.